Penerapan Model Pembelajaran Project Based Learning (PjBL) pada Materi Energi Terbarukan di SMAN 3 Pandeglang - Suhartini, Heni (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
The results of the 2023 SMAN 3 Pandeglang education report card show that literacy skills are in the Medium category (44.44% of students have achieved minimum competency) meaning that 40% - 70% of students have achieved minimum competency for reading literacy but efforts need to be made to encourage more students in achieve minimum competency.The use of the PjBL learning model is expected to increase social interaction between students and achieve higher student learning outcomes compared to competitive learning or individualistic learning which usually occurs. Most of the teaching and learning activities at SMAN 3 Pandeglang still use the lecture method or are not PjBL based.Based on the explanation above, it is necessary to carry out an in-depth study of improving students' scientific literacy abilities through the application of the Project Based Learning (PjBL) learning model on Renewable Energy material at SMAN 3 Pandeglang